2021
DOI: 10.1038/s41440-021-00719-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of the ratio of visceral-to-subcutaneous fat volume with renal function among patients with primary aldosteronism

Abstract: Patients with primary aldosteronism have a higher risk of chronic kidney disease. Visceral fat tissue is hypothesized to stimulate the adrenal glands to overproduce aldosterone, and aldosterone promotes visceral fat tissue to produce inflammatory cytokines. However, it is unclear whether the volume of accumulated visceral fat tissue is associated with renal impairment among patients with hyperaldosteronism. We conducted a single-center cross-sectional study to assess the association between the estimated glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Furthermore, in the PA group with a high plasma aldosterone concentration (PAC), the VFV/SFV ratio was significantly and positively correlated with the E/e' ratio. The authors previously showed that a higher VFV/SFV ratio was correlated with impaired renal function in PA patients [5]. Taking these reports together, the greater the visceral fat mass is, the more prevalent cardiovascular complications are.…”
mentioning
confidence: 88%
“…Furthermore, in the PA group with a high plasma aldosterone concentration (PAC), the VFV/SFV ratio was significantly and positively correlated with the E/e' ratio. The authors previously showed that a higher VFV/SFV ratio was correlated with impaired renal function in PA patients [5]. Taking these reports together, the greater the visceral fat mass is, the more prevalent cardiovascular complications are.…”
mentioning
confidence: 88%
“…Thu et al from Singapore [Supplementary Information 8 - 3 ] found a positive association between accumulated visceral adipose tissue and systolic BP in midlife-aged women, independent of burdens of inflammatory markers. Intriguingly, Haze et al [ 131 ] clearly demonstrated that an increased ratio of visceral-to subcutaneous fat volume was an independent risk factor for renal dysfunction in Japanese patients with primary aldosteronism. These findings should highlight the clinical importance and the need for further research to explore surrogate markers of obesity in the care of hypertension and its related conditions (Fig.…”
Section: Optimal Therapy and Clinical Management Of Obesity/diabetes ...mentioning
confidence: 99%